Expand your knowledge base with the help of IDNLearn.com's extensive answer archive. Discover prompt and accurate responses from our experts, ensuring you get the information you need quickly.
Sagot :
Sure, let's go through the steps to find the antiderivative [tex]\( F(v) \)[/tex] of the function [tex]\( f(v) = \frac{3}{4} \sec(v) \tan(v) \)[/tex] that satisfies the condition [tex]\( F(0) = 3 \)[/tex].
### Step 1: Find the Antiderivative
First, we need to find the indefinite integral of the function [tex]\( f(v) \)[/tex]:
[tex]\[ \int \frac{3}{4} \sec(v) \tan(v) \, dv \][/tex]
We know that the derivative of [tex]\( \sec(v) \)[/tex] is [tex]\( \sec(v) \tan(v) \)[/tex], so integrating [tex]\( \sec(v) \tan(v) \)[/tex] gives [tex]\( \sec(v) \)[/tex]. Thus:
[tex]\[ \int \sec(v) \tan(v) \, dv = \sec(v) \][/tex]
Considering the constant multiplier [tex]\(\frac{3}{4}\)[/tex], the integral becomes:
[tex]\[ \int \frac{3}{4} \sec(v) \tan(v) \, dv = \frac{3}{4} \sec(v) \][/tex]
Thus, the antiderivative [tex]\( F(v) \)[/tex] can be written as:
[tex]\[ F(v) = \frac{3}{4} \sec(v) + C \][/tex]
### Step 2: Determine the Constant of Integration
To determine the constant [tex]\( C \)[/tex], we use the condition [tex]\( F(0) = 3 \)[/tex]:
[tex]\[ F(0) = \frac{3}{4} \sec(0) + C = 3 \][/tex]
We know that [tex]\( \sec(0) = 1 \)[/tex], so:
[tex]\[ \frac{3}{4} \cdot 1 + C = 3 \][/tex]
This simplifies to:
[tex]\[ \frac{3}{4} + C = 3 \][/tex]
Subtract [tex]\(\frac{3}{4}\)[/tex] from both sides to solve for [tex]\( C \)[/tex]:
[tex]\[ C = 3 - \frac{3}{4} = \frac{12}{4} - \frac{3}{4} = \frac{9}{4} = 2.25 \][/tex]
### Step 3: Write the Final Antiderivative
Now that we have determined [tex]\( C = 2.25 \)[/tex], we can write the final expression for the antiderivative [tex]\( F(v) \)[/tex]:
[tex]\[ F(v) = \frac{3}{4} \sec(v) + 2.25 \][/tex]
Thus, the antiderivative [tex]\( F \)[/tex] that satisfies the given condition is:
[tex]\[ F(v) = 2.25 + \frac{3}{4} \sec(v) \][/tex]
So we fill in the blank:
[tex]\[ F(v) = \boxed{2.25 + \frac{3}{4} \sec(v)} \][/tex]
### Step 1: Find the Antiderivative
First, we need to find the indefinite integral of the function [tex]\( f(v) \)[/tex]:
[tex]\[ \int \frac{3}{4} \sec(v) \tan(v) \, dv \][/tex]
We know that the derivative of [tex]\( \sec(v) \)[/tex] is [tex]\( \sec(v) \tan(v) \)[/tex], so integrating [tex]\( \sec(v) \tan(v) \)[/tex] gives [tex]\( \sec(v) \)[/tex]. Thus:
[tex]\[ \int \sec(v) \tan(v) \, dv = \sec(v) \][/tex]
Considering the constant multiplier [tex]\(\frac{3}{4}\)[/tex], the integral becomes:
[tex]\[ \int \frac{3}{4} \sec(v) \tan(v) \, dv = \frac{3}{4} \sec(v) \][/tex]
Thus, the antiderivative [tex]\( F(v) \)[/tex] can be written as:
[tex]\[ F(v) = \frac{3}{4} \sec(v) + C \][/tex]
### Step 2: Determine the Constant of Integration
To determine the constant [tex]\( C \)[/tex], we use the condition [tex]\( F(0) = 3 \)[/tex]:
[tex]\[ F(0) = \frac{3}{4} \sec(0) + C = 3 \][/tex]
We know that [tex]\( \sec(0) = 1 \)[/tex], so:
[tex]\[ \frac{3}{4} \cdot 1 + C = 3 \][/tex]
This simplifies to:
[tex]\[ \frac{3}{4} + C = 3 \][/tex]
Subtract [tex]\(\frac{3}{4}\)[/tex] from both sides to solve for [tex]\( C \)[/tex]:
[tex]\[ C = 3 - \frac{3}{4} = \frac{12}{4} - \frac{3}{4} = \frac{9}{4} = 2.25 \][/tex]
### Step 3: Write the Final Antiderivative
Now that we have determined [tex]\( C = 2.25 \)[/tex], we can write the final expression for the antiderivative [tex]\( F(v) \)[/tex]:
[tex]\[ F(v) = \frac{3}{4} \sec(v) + 2.25 \][/tex]
Thus, the antiderivative [tex]\( F \)[/tex] that satisfies the given condition is:
[tex]\[ F(v) = 2.25 + \frac{3}{4} \sec(v) \][/tex]
So we fill in the blank:
[tex]\[ F(v) = \boxed{2.25 + \frac{3}{4} \sec(v)} \][/tex]
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Your search for answers ends at IDNLearn.com. Thank you for visiting, and we hope to assist you again soon.